An overview of legal framework for personal data protection on electronic voting in Indonesia - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (Kuala Lumpur International Business, Economics and Law Conference, 2013)
Indonesia has launched the implementation of e-KTP to improve demography data for the purpose of eliminating the data redundancy and inaccuracies data of population, which was organized by Ministry of Home Affairs. It expected to enhance the quality of the statistic to support government policy and decision-making. In aligning with this implementation, there is a tendency and wishes to implement e-Voting for next election because it offers tremendous benefit to the society especially regards speed, accuracy and cost savings. Further, the primary concern of e-Voting to protection personal data of the voters for improving the quality of election than previous one. Nonetheless, the existing regulation in Indonesia still has been sadly lacking for mechanism and techniques. This paper provides the review for current legal framework in protecting personal data in Indonesia to be used especially for e-Voting purpose. Thereby, it brings the focus towards whole aspect of situation before, during and after the election, which should be considered by legal regulation by identifying the potential threats.